Experimental Study: Unveiling the Impact of Interactive Learning Media on Mastering Basic Electronics and Electrical Measurement Instruments at SMK Negeri 2 Payakumbuh - Lara Agustiana; Efrizon; Hanesman; Dedy Irfan (Sagamedia Teknologi Nusantara, 2023)
This study employs a quantitative approach with an experimental design. The main objective is to determine the influence of interactive learning media on the Fundamentals of Electronics among students studying electrical measuring instruments, electronics, and instrumentation at SMK Negeri 2 Payakumbuh. The research population consists of students from the X TAV 1 and X TAV 2 classes at SMK N 2 Payakumbuh for the academic year 2023/2024, totaling 61 students. The research instrument used was a set of objective questions administered at the end of the learning process after each treatment. The results indicate that the calculated t-value exceeds the critical t-value (4.60 > 1.67). This implies that the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Therefore, it can be concluded that the use of interactive learning media significantly affects students' learning outcomes in the study of electrical measuring instruments, electronics, and instrumentation at SMK Negeri 2 Payakumbuh.